Exploring the relationship between meaning at work and subjective wellbeing among language teachers - Behruz Lotfi Gaskaree; Ismail Xodabande; Mohammad Zohrabi; Nastaran Behshad (Australian Journal of Applied Linguistics)
The concept of meaning at work has gained significant attention in organizational psychology. As teaching is a profession often associated with high levels of emotional investment and personal engagement, understanding how the perception of meaning in work influences teachers’ wellbeing is crucial. This study aimed to explore the relationship between meaning at work and subjective wellbeing among English as a Foreign Language (EFL) teachers. It sought to quantify this relationship through regression analysis and further elucidate it through thematic analysis of qualitative interview data. The study involved 65 EFL teachers, with data collected via the Work and Meaning Inventory (WAMI) and the Subjective Well-being Scale. Linear regression analysis was used to examine the relationship between meaning at work and subjective wellbeing. Additionally, in-depth interviews with 12 teachers provided qualitative insights, analyzed through thematic analysis to identify emergent themes relating to meaning at work and its impact on wellbeing. Regression analysis revealed a significant positive relationship between meaning at work and subjective wellbeing (R² = .394, p < .001). The thematic analysis of interview data yielded four main themes: personal fulfillment and job satisfaction, professional growth and self-realization, sense of purpose and contribution to society, and connection and relationships. These themes underscored the multifaceted ways in which meaning at work contributes to language teachers’ wellbeing. The study highlights the profound impact of meaning at work on EFL teachers' subjective wellbeing. The findings emphasize the importance of fostering meaningful work environments in educational settings to enhance teacher wellbeing, with implications for teacher retention, job satisfaction, and overall school climate.